INTERTEXTUALITY IN THE MODERN RUSSIAN POETRY - Zinurova, E.S. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Literaturovedenie, zhurnalistika, 2017)
The article presents the analysis of specific manifestations of intertextuality in the Russian poetry of the late XX - early XXI ages. In the introduction, the author gives a short review of the theoretical aspect of the theme - the nature of intertextuality. In the main part author derives a hypothesis that there are obvious dialogical relations between modern and classic poets. The basic forms of creative interaction are regarded in this aspect. The author analyzes lyrics of “innovators” and “archaists” among the poets of the turn of the XX-XXI centuries. The conclusion is made of the difference in the intertextual poetics of the creative works between the followers of the classical or modernist methods of poetic expression. The author’s reasoning and conclusions are based on analytical publications in recent years and the works of famous and little-known poets.